Democratic regional head elections are based on the principles of freedom, openness, honesty and fairness - Akili, Wahyudin M.; Nur, Rafika; Marwan, Marwan (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
Direct regional elections are a concrete manifestation of the formation of democratization in the regions. Direct regional head elections must be included in the larger framework for realizing democratic local government. The aim of holding direct regional elections is to form a strong government based on the choice and legitimacy of the people. Direct regional elections are a concrete manifestation of the formation of democratization in the regions. The type of research used is empirical normative legal research, this type of research combines normative law which is supported by information from empirical data. Application of normative legal provisions in action in every specific legal event that occurs in society. Direct regional head election is a necessity to correct deviations in the implementation of regional autonomy shown by elites at the local level. Holding honest, fair and clean elections